170k views
2 votes
When 0.3(4x – 8) – 0.5(–2.4x + 4) is simplified, what is the resulting expressions

-4.4
1.2x-2.4+1.2x-2
2.4x-0.4
2.4x-4.4

User Rop
by
5.7k points

1 Answer

11 votes

Answer:


2.4x-4.4

Explanation:

Given the following question:


0.3(4x-8)-0.5(-2.4x+4)

To simplify the expression, we are going to need to rewrite the expression by expanding the terms and then solve by using the distributive property. Then we combine like terms in till the expression can no longer be simplified to find our answer.


0.3(4x-8)-0.5(-2.4x+4)

0.3(4x-8)

0.3*4=1.2x

0.3*4=2.4

1.2x-1.2-0.5(-2.4x+4)

-0.5(-2.4x+4)

-0.5*-2.4=1.2

-0.5*4=-2

1.2-2

1.2x-2.4+1.2x-2

1.2+1.2=2.4x

-2.4+-2=-4.4

=2.4x-4.4

Your answer is "2.4x - 4.4."

Hope this helps.

User Siim Kallari
by
5.4k points